Structure and functions of a metallo-beta-lactamase- like hypothetical protein bleg1_2437 from alkali-tolerant soil bacterium Bacillus lehensis G1 - Tan, Soo Huei (2015)
β-lactam antibiotics are the most useful chemotherapeutic agents in the treatment of diseases of bacterial origin. However, the emergence of antibiotic resistance mechanism among pathogenic bacteria has downsized the efficacy of antibiotics via the production metallo-β-lactamase (MBL) which enables pathogens to destroy the β- lactam ring of β-lactam antibiotics. Although MBL is not ubiquitously found in all pathogenic bacteria, its presence is a public health concern. In addition, the presence of unknown and uncharacterised MBL in the environment signal the possible emergence of ―seilnt‖ superbug. Therefore, the study aimed to identify a functional cluster of Hypothetical proteins (HPs) and screen the HP pool for the presence of MBL domain from the locally isolated Bacillus lehensis G1 via in silico prediction. Furthermore,predicts the structure and function of the selected HP and characterise the antibioticdegrading ability of the selected HP. In the present study, there are 1202 hypothetical proteins (HPs) have been discovered from newly sequenced genome of alkali-tolerant soil bacterium B. lehensis G1, HP Bleg1_2437 may likely be an MBL. Domain and sequence analysis of HP Bleg1_2437 using InterProScan and DELTA-BLAST revealed that this 23 kDa protein contains highly conserved metal-binding residues such as H54, H56, D58, H59, H131 and H191 that are similar with the those in subclass B3 of MBL that are involved in the coordination of two Zn2+ ions. The three-dimensional protein structure of Bleg1_2437 built using Modeller 9v10 exhibited an αββα sandwich layer similar to the well conserved global topology of MBL superfamily. Docking of several β-lactam antibiotics to the predicted structure of Bleg1_2437 using Maestro v9.3 evealed that the antibiotics interact with residues in the binding pocket of Bleg1_2437 such as the Zn2+ binding residues mentioned above, hydrophobic residues such as I10,Y15, F153, I157 and G158, as well as polar residues such as Q11, T12, N13, D150 and S156 with significant binding energy. The ORF of Bleg1_2437 with approximately 633 nucleotides was amplified by PCR and cloned into pET-32(b) to form pET- 32(b)::Bleg1_2437 recombinant plasmid. This recombinant plasmid was transformed into Escherichia coli Rosetta-gami (DE3) for Bleg1_2437 protein expression and purification. The optimum condition for intracellular expression of Bleg1_2437 was achieved at 20 ºC, with Isopropyl-β-D-Thiogalactopyranoside (IPTG) concentration of 0.1 mM and incubated for 18 hours. The crude extract of Bleg1_2437 was purified through Hi-Trap Sepharose affinity chromatography.The yield of purified recombinant Bleg1_2437 with protein tags (Trx-tag + S-tag + His-tag) was about 22 %. It displayed hydrolysis activity towards several β-lactam antibiotics with preference towards ampicillin. It exhibited the highest catalytic efficiency kcat/Km (86.4 μM-1s-1) towards ampicillin compared with meropenem (16.9 μM-1s-1) and nitrocefin (5.0 μM-1s-1). Furthermore, with the addition of 100 μM of zinc sulfate, the kcat/Km values of Bleg1_2437 towards all tested β-lactam antibiotics were increased approximately 2 to 5 fold. The findings of this study reveal on the presence of the clinically important and dangerous antibiotics-degrading enzyme, MBL, within the pool of HPs which are generally regarded as proteins of unknown functions and of no particular importance.